Biosphere reserve zones are equal in terms of katydid ecoacoustics. Issue 3 (3rd May 2020) - Thompson, Aileen C.; Samways, Michael J.; Bazelet, Corinna S.
ABSTRACT: Globally, biosphere reserves (BRs) conserve biodiversity across a gradient of human disturbance, yet there is very little empirical research investigating the effectiveness of BRs. The aim here is to compare katydid song diversity and abundance across the three zones of the Kogelberg BR using acoustic monitoring techniques. An index of Acoustic Activity was used to determine katydid abundances from recordings. Only eight katydid species were recorded over the entire summer season, with the species accumulation curve reaching an asymptote. Katydid diversity and abundances were very similar across the three zones. Habitat quality had a greater effect on abundance than on species richness. No single katydid species was identified as a bioindicator, rather the entire assemblages are responsive to habitat quality. The low diversity of katydids relative to other biomes and to other insects within the KBR appears to come from a long history of fire and extreme weather events, as is the case for other vegetation dependent insect taxa in the region. While we expect lower biodiversity away from the BR core zone, some groups, like these katydids, are maintained equally well in the three zones, and have not to date been adversely affected by human activity.